(untitled) (Acta Entomológica Chilena, 2022)
A new species of the genus Arthrobrachus Solier is described, A. epumenki n.sp. The specific ñame, based on mapudungun language allude to a pair of short bristles tufts on metasternal surface of male. Geographic distribution is provided.